Analisis Semiotik pada Puisi “Makna Sebuah Titipan” Karya W.S. Rendra - Junifer Siregar (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aims to describe the semiotic elements contained in the poems "The Meaning of a Custody" and "The Poor" by WS Rendra and to describe the semiotic meaning contained in the poems "The Meaning of a Custody" and "People Poor” by WS Rendra. Based on the semiotic analysis of the poem "The Meaning of a Custody" by W.S. Rendra, there are language styles such as Climax, Rhetoric, Association, Anticlimax, Personification and Irony. Based on the semiotic analysis of the poem "The Poor" by W.S. Rendra, there are language styles such as Rhetoric, Association, Anticlimax, Personification and Irony. Semiotics the poem "The Meaning of a Custody" tells about something that a person has is just a deposit or a gift from God, so it needs to be grateful and don't be arrogant, while the poem "The Poor" tells Rendra describing the condition of poor people who are very concerned.